Migrant death: border safety and situational crime prevention on the US-Mexico divide - Guerette, Rob T. (Criminal justice recent scholarship, 2007)
Introduction -- The nature of illegal immigration in the United States -- Purpose, history, and function of the United States Border Patrol -- The issue of migrant deaths -- Preventing migrant deaths : ethics, policy, and the utility of situational crime prevention -- Impact of border safety initiative policy -- Understanding the circumstance and situational nature of migrant deaths -- Implications for policy, practice, and future research